Qualidade química da água residual da criação de peixes para cultivo de alface em hidroponia - Cortez, Glauco E. P.; de Araújo, Jairo A. C. [UNESP]; Bellingieri, Paulo A. [UNESP]; Dalri, Alexandre B. (FapUNIFESP (SciELO), 2009)
Aiming to evaluate the association of hydroponic lettuce cultivation with residues from a fish intensive breeding system, a project was carried out in the Aquaculture Center in the FCAV-UNESP at Jaboticabal, SP, Brazil. A closed system was designed in order to allow the water to circulate through the fish tanks, a clarifier tank for removal of residues, a reservoir for biological conversion of ammonia into nitrate, and the hydroponic system. After this process, water returned back to the fish tanks. Three varieties of lettuce, constituting the treatments with four repetitions were evaluated. The results of the chemical analysis of the residual water from the fish tanks indicated the presence of the majority of the mineral nutrients necessary for vegetable development. Their concentration was close to that found in nutrient solutions, used for lettuce hydroponic cultivation, except for potassium and magnesium. The low concentration of magnesium in the water did not prevent lettuce development, although the plants presented visual symptoms of deficiency of this nutrient. Differences were not found between the varieties produced, regarding productivity and the mean weight of fresh plants.
Chemical quality of residual water from fish breeding tanks for cultivation of hydroponic lettuce
Keywords: Brycon cephalus; Lactuca sativa; Recirculating systems; Lactuca